2014
DOI: 10.5194/gmd-7-1467-2014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously assimilating multivariate data sets into the two-source evapotranspiration model by Bayesian approach: application to spring maize in an arid region of northwestern China

Abstract: Abstract. Based on direct measurements of half-hourly canopy evapotranspiration (ET; W m−2) using the eddy covariance (EC) system and daily soil evaporation (E; mm day−1) using microlysimeters over a crop ecosystem in arid northwestern China from 27 May to 14 September in 2013, a Bayesian method was used to simultaneously parameterize the soil surface and canopy resistances in the Shuttleworth–Wallace (S–W) model. Four of the six parameters showed relatively larger uncertainty reductions (> 50%), and their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 93 publications
3
41
0
Order By: Relevance
“…We constructed a Bayesian inference framework to optimize the key parameters using the flux data sets simultaneously. But, an important issue in optimization is equifinality, where the same result might be caused by different parameter combinations [ Franks et al ., ; Zhu et al ., ]. Engeland et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a Bayesian inference framework to optimize the key parameters using the flux data sets simultaneously. But, an important issue in optimization is equifinality, where the same result might be caused by different parameter combinations [ Franks et al ., ; Zhu et al ., ]. Engeland et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to the Bayes theorem, the posterior probability density function (PDF) of model parameters is proportional to their prior PDF and the likelihood function and can be calculated as p()θtrue|Op()Otrue|θp()θ where θ are the parameter sets; O are the observed data sets; p ( θ | O ) is the posterior probability distribution; p ( θ ) is the prior probability distribution of parameter θ , which is chosen as uniform distributions with specified prior ranges (Table ); and p ( O | θ ) is the likelihood function, which reflects the influence of the observation data sets on parameter identification. The likelihood function can be expressed as [ Zhu et al ., ] p()O()ttrue|θ=truetrue∏t=1normalT12πσ2normalexp()prefix−[]O()tS()t22σ2 where T is the total length of observation; O ( t ) and S ( t ) are observed and simulated values at time t ( t = 1, 2, …, T ), respectively; and σ is the standard deviation of the model error that is assumed to be unchanged during the observation time [ Braswell et al ., ], and σ can be expressed as σ=1Ttruetrue∑t=1TOtSt2 …”
Section: Model and Methodsmentioning
confidence: 98%
“…That is, very different combination of the parameter values (“trade‐off” between the parameters) can make the model generate similar total ET predictions, but with great uncertainties in the model's ET partitioning. This phenomenon is well known as equifinality or parameter identifiability (Beven & Freer, ; Zhu et al, , ). Thus, we cannot ensure the model's ET partitioning based on a single set of optimized parameters to be correct, even though the simulated total ET were in good agreement with measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the influence of model parameters on model response is significant elements in the development of robust regional and global ET products (Bastola, Murphy, & Sweeney, ; Brigode, Oudin, & Perrin, ; McCabe et al, ; Zhang et al, ; Zhu et al, ). Previous studies have shown that model parameters may vary by PFTs and species because of the genetic or local environmental variation (Mu, Zhao, & Running, ; Wullschleger et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation